2022
DOI: 10.3390/s22218453
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Design of a Quad-Stable Piezoelectric Energy Harvester via Bifurcation Theory

Abstract: The parameter tuning of a multi-stable energy harvester is crucial to enhancing harvesting efficiency. In this paper, the bifurcation theory is applied to quantitatively reveal the effects of structural parameters on the statics and dynamics of a quad-stable energy harvester (QEH). Firstly, a novel QEH system utilizing the geometric nonlinearity of springs is proposed. Static bifurcation analysis is carried out to design quad-stable working conditions. To investigate the cross-well and high-energy vibration, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The idea to exploit multi-stability was further developed and generalized, introducing tri-stable [77][78][79] and, more generally, multi-stable energy harvesters [80][81][82][83][84][85]. In [77] it was shown that a tri-stable arrangement passes easily through potential wells, generating higher energy output over a wider range of frequency with respect to a bi-stable setup with a deeper potential well.…”
Section: Nonlinear Harvester Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea to exploit multi-stability was further developed and generalized, introducing tri-stable [77][78][79] and, more generally, multi-stable energy harvesters [80][81][82][83][84][85]. In [77] it was shown that a tri-stable arrangement passes easily through potential wells, generating higher energy output over a wider range of frequency with respect to a bi-stable setup with a deeper potential well.…”
Section: Nonlinear Harvester Modelingmentioning
confidence: 99%
“…It was shown that such a solution not only reduced the potential energy barrier and the threshold of snapthrough, but also broadened the bandwidth of inter-well motion. In [80], an ingenious setup, where the inertial mass on the top of a cantilever beam is connected to a support through three springs, was proposed. The resulting structure exhibits four steady state responses and dozens of primary resonance modes.…”
Section: Nonlinear Harvester Modelingmentioning
confidence: 99%
“…For VEHs, the geometric configuration of linear springs in the oscillators can be effective in broadening the frequency band of the resonance, thereby showing effective qualities in improving the performance of VEHs [8][9][10]. The most commonly used oscillator is the smooth and discontinuous (SD) oscillator [11,12]. It consists of a lumped mass and a pair of symmetrically inclined springs, as can be seen in the primary structure of the VEH in Figure 1a.…”
Section: Introductionmentioning
confidence: 99%